28‐3: Mini‐LED Backlight for HDR Compatible Mobile Displays. Issue 1 (29th May 2019) - Masuda, Takeshi; Watanabe, Hisashi; Kyoukane, Youzou; Yasunaga, Hirotoshi; Miyata, Hidekazu; Yashiki, Masafumi; Nara, Tomoyuki; Ishida, Takeshi
Abstract : Recently, ultra‐thin and direct lit‐type backlights with a 2‐dimensional local dimming function have become increasingly of interest because of increasing demands for HDR compatible LCDs for mobile terminals. In this paper, we present a newly developed Mini‐LED backlight that offers an effective solution to these demands.